Praktyka revocatoria del mandato w Argentynie - Kossak, Dominik (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
Although first regulations concerning revoctoria del mandato appeared in Argentina almost a hundred years ago, the practice of it dates back only over a dozen years. It is restricted strictly to a local level, not the central regulations. Based on Argentinean law, we can systematize revoctoria del mandato in the following way: firstly, based on requirements put on ones wanting to organize referendum; secondly, in which normative acts this issue is regulated and on whose initiative this revoctoria del mandato is carried out. A few of recently finished procedures show the substance of direct democracy. What happened in San Carlos de Bariloche is a great example of battle via referenda between the mayor and councillors, which resulted in revocation of the former. This complex case allows us to fully understand how exactly revocation del mandato works. As we look at a few more of these referenda, we can clearly see the whole picture of Argentinean practice. Moreover, it is an institution which can have great success in local communities. Unfortunately, it is also being used mainly by politicians to achieve their goals, which contradicts with its purpose.
Keywords: podpisy; Recall; samorząd; referendum; polityka; Argentyna